2013
DOI: 10.1117/12.2023475
|View full text |Cite
|
Sign up to set email alerts
|

Fast manufacturing of E-ELT mirror segments using CNC polishing

Abstract: We report on the first-ever demonstration of grinding and polishing full-size, off-axis aspheric, mirror segments as prototypes for an extremely large telescope, processed entirely in the final hexagonal shape. We first describe the overall strategy for controlling form and mid spatial frequencies, at levels in the vicinity of <10nm RMS surface. This relies first on direct CNC grinding of the base-form of these 1.4m segments, using the Cranfield BoX TM machine. The segments are then mounted on a custom designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, it needs a high-precision reference sphere, which is costly and complex. Comley et al [1] and Gray et al [11] reported the profile data of E-ELT segments (1.4 m size) measured with an off-machine Leitz CMM. Su and co-workers investigated a swing arm profilometer for in situ measurement of aspherics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it needs a high-precision reference sphere, which is costly and complex. Comley et al [1] and Gray et al [11] reported the profile data of E-ELT segments (1.4 m size) measured with an off-machine Leitz CMM. Su and co-workers investigated a swing arm profilometer for in situ measurement of aspherics.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported [4] on successful completion, at the National Facility for Ultra Precision Surfaces, of a 1.4 m Master Spherical Segment (R = 84 m), which is used as a comparator to assert segment-matching and absolute radius-ofcurvature. We have also described completion of three 1.4 m across-corners, hexagonal, off-axis aspheric mirror segments, with formal acceptance [5]. CNC grinding was performed using the BOX™machine [6] at Cranfield University.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we report on a new approach [5]. Ultra-precision bound-abrasive CNC machining of the off-axis asphere, and then smoothing, polishing and form-correction, are all performed on the blank in its final hexagonal state.…”
Section: Introductionmentioning
confidence: 99%